Characterization of Protease Enzyme Produced from Locally Isolated Bacillus sp. - Shareef, Saja Ali; Husein, Zainab Ali (Journal for Research in Applied Sciences and Biotechnology, 2022)
This study aimed to characterization of protease enzyme purified from locally isolated Bacillus sp.. A total of 50 soil samples were taken for this purpose. Only 35 (or 70%) of the sample were found to have given rise to bacterial growth. As the first phase in the cultivation of bacteria, the samples were grown on mannitol egg yolk polymyxin agar and nutrition agar. More than 20 bacterial isolates were discovered, according to the findings. The results of the cultural, microscopic, and biochemical examinations used to identify these isolates revealed that 15 of them were Bacillus spp. Additionally, the use of the Vitek 2 technique ensured that each of the 15 isolates belonged to this species. Examining these isolates' capacity to create proteases revealed that all 15 of the Bacillus sp. isolates were capable of doing so, albeit to varying degrees. The isolate with the number S9 was the best at producing proteases, with a specific activity value of 40.19 U/mg proteins. On a casein hydrolyzed medium plate with a diameter of 3.0 mm and 2.2 mm, respectively, they demonstrated a clean zone. After 42 hours and 72 hours of incubation at 37°C, respectively, the strain 9 produces 1.01 units of proteolytic enzyme per milliliter. Proteolytic activity decreases with longer incubation times. It has potential for industrial use because the isolated Bacillus sp. was generating protease.